2009
DOI: 10.1016/j.ajog.2009.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid ploidy in endometrial carcinoma: a reproducible and valid prognostic marker in a routine diagnostic setting

Abstract: DNA ploidy estimation in endometrial carcinoma adds independent prognostic information in a routine diagnostic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 355 publications
(505 reference statements)
1
34
0
1
Order By: Relevance
“…MSS-aneuploid subtype tumors had pathological features similar to those of MSI tumors, since they frequently presented higher grade, advanced stage and vascular involvement. The association of aneuploidy with a more aggressive clinical phenotype in EC is well documented [4, 27, 28]. According to our data, MSS-diploid tumors display a more benign phenotype (differentiated grade, early stage and absence of vascular invasion) compared to MSI and MSS-aneuploid tumors.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…MSS-aneuploid subtype tumors had pathological features similar to those of MSI tumors, since they frequently presented higher grade, advanced stage and vascular involvement. The association of aneuploidy with a more aggressive clinical phenotype in EC is well documented [4, 27, 28]. According to our data, MSS-diploid tumors display a more benign phenotype (differentiated grade, early stage and absence of vascular invasion) compared to MSI and MSS-aneuploid tumors.…”
Section: Discussionsupporting
confidence: 70%
“…Conversely, several groups have referred an association of MSI with better [23, 24], or worse [25] outcome in series including only endometrioid tumors or both histological types. As for the prognostic value of ploidy in EC, latest publications suggest that is a statistically independent prognosticator of poor outcome through multivariate analysis [4, 27, 28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…132 Small-scale studies 163 Regarding plasma level of GDF-15, further studies are needed to explore the applicability of GDF-15 measurements as a marker for stratification for lymph node sampling or for early detection of recurrence in routine follow-up.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Tumor DNA ploidy, a relatively objective parameter, has been shown to be an important prognostic marker for patients with EC in several studies (7)(8)(9)(10)(11), outperforming even surgical staging (9), and has been suggested as a predictive factor when included in treatment planning (12,13). Patients with DNA diploid EC have significantly lower death rates and longer recurrence-free survival compared with those with DNA aneuploid tumors (7,9,14,15).…”
mentioning
confidence: 99%